Does Social Media Engagement Moderate Brand Engagement and Brand Loyalty? Evidence from Young Consumers of Malaysian Modest Fashion Industry - Ahmad, Zulkarnian; Suhana Menon, Ami; Mason, Cordelia; Farid Shamsudin, Mohd; Sentosa, Ilham (International Journal of Psychosocial Rehabilitation, 2020)
The significance of branding in marketing activities is well established. The sustainability of products and services is highly dependent on the vendor’s ability to create and maintain a brand. Brand loyalty has been linked to variables such as brand personality, perceived value, and brand engagement. What is the relationship between brand engagement and brand loyalty? How does social media affect this relationship? A sample of 400 respondents was surveyed to establish the relationship between brand engagement and brand loyalty and to find out the role of social media. Pitching five dimensions of brand engagement, i.e., identification, interaction, absorption, enthusiasm, and attention, to two dimensions of brand loyalty, i.e., behaviour and attitude, the role of social media was explored using four dimensions, which are brand usage intent, social presence, electronic word of mouth, and social brand engagement. The motivation to focus on young consumers is the assumption that they will flood the market as soon as they are gainfully employed. The result was unexpected. Contrary to common perception, the results show that social media engagement does not moderate the relationship. A focus group discussion among a sample of respondents was conducted for triangulation. The insights of the triangulation will be shared in the presentation.